Clean extraction of pectin from dragon fruit peels, pomelo peels, okra, and pineapple peels using deep eutectic solvents and ionic liquids - Haniman, Adilan; Elgharbawy, Amal A.M.; Hayyan, Adeeb; Wae-Hayee, Makatar; Mohd Noor, Nurul Auni; Jawahar, Bassam Mohamed; Hussain, Mahmud; Dewi, Ika Atsari (IIUM Press, 2024)
Pectin is the main constituent of fruit peels that contributes to the fruit's solid and firm shape. Having wide applications in the food, pharmaceutical, and cosmetics industries, its extraction from bioresources would mark a sustainable advancement in biotechnology. The biomaterials for pectin extraction targeted in the study were dragon fruit peels (Hylocereus costaricensis), Pomelo peels (Citrus grandis), okra (Abelmoschus esculentus), and pineapple peels (Ananas comosus). Aqueous extractions of pectin from fruit peels were performed in a sono-reactor using deep eutectic solvents (DESs). Ionic liquids such as (Choline acetate ≥ 95%) [Ch][Ac] and (1-ethyl-3-methylimidazolium acetate ≥ 97%) [EMIM][Ac] were also employed as extraction solvents. Morphological screening with the electron microscope (SEM) and FTIR showed that the extracted pectin had a similar surface as commercial pectin. The extracted pectin can completely dissolve in water to form a homogenous suspension. The pectin yield from dragon fruit peels was 60±2.00 wt% with a degree of esterification at about 66-72%. This study introduces a clean extraction that can potentially substitute solvents in the pectin industry.